Snop-3 pulse generator; Instruments and Experimental Techniques; Vol. 30, iss. 6 pt. 1 - Kovsharov N. F.; Luchinskii A. V.; Mesyats G. A. Gennady Andreyevich; Sorokin S. A.; Fedushchak V. F.; Ratakhin N. A. Nikolay Aleksandrovich (1988, 1988)
The Snop-3 pulse generator provides a current rise time of approximately 4 to 103 A/sec in an inductive lead (30 nH) with a current amplitude of up to 2 MA. The generator has a power equal to or greater than TW for loads of the multiwire liner type. The generator consists of primary energy storage (capacitor bank), a pulse transformer, intermediate storage, a shaping line, and a transmission line. Energy is transmitted sequentially from low-frequency to high-frequency resonant LC circuits in order to increase the power. Commutation between the intermediate storage and the shaping line is performed with a water-filled discharger in both a controlled and uncontrolled fashion. Commutation between the shaping and transmission lines is not controlled.